2015
DOI: 10.1093/carcin/bgv163
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of RECQL5 helicase expression in breast cancers

Abstract: RECQL5 is a member of the RecQ family of DNA helicases and has key roles in homologous recombination, base excision repair, replication and transcription. The clinicopathological significance of RECQL5 expression in breast cancer is unknown. In this study, we have evaluated RECQL5 mRNA expression in 1977 breast cancers, and RECQL5 protein level in 1902 breast cancers [Nottingham Tenovus series (n = 1650) and ER- cohort (n = 252)]. Expression levels were correlated to aggressive phenotypes and survival outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 33 publications
5
27
2
Order By: Relevance
“…An interesting observation was that we did not observe any cytoplasmic staining for RECQL1. This is in contrast to the cytoplasmic staining observed for BLM, RECQL4 and WRN in breast cancers (16, 38, 39). The data suggests differential regulation of localisation for different RecQ helicases.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…An interesting observation was that we did not observe any cytoplasmic staining for RECQL1. This is in contrast to the cytoplasmic staining observed for BLM, RECQL4 and WRN in breast cancers (16, 38, 39). The data suggests differential regulation of localisation for different RecQ helicases.…”
Section: Discussioncontrasting
confidence: 88%
“…We have recently investigated the expression of RECQL4, RECQL5, BLM and WRN in breast cancers (17, 39-41). Whereas high RECQL4, high RECQL5 and high BLM expression were associated with aggressive breast cancers (17, 39, 40), low WRN expression was linked to poor outcomes (41). Interestingly, RecQ helicase mRNA levels are linked to biologically distinct integrative clusters reported in the METABRIC study (15).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a large scale expression profiling of RECQL5 in human breast cancer showed that high expression of the helicase is often associated with bad tumor grades and poor prognosis. 38 In line with that, our analysis of RECQL5 expression data also suggests that higher levels of expression are correlated with poorer prognosis of TNBC patients ( Figure 5E). These observations suggest that RECQL5 could also function as an oncogene.…”
Section: Discussionsupporting
confidence: 87%
“…However, we were able to identify a recurrent high-impact mutation in the gene RECQL5 , a DNA helicase involved in interstrand crosslinking repair [ 55 , 73 ]. RECQL5 is essential for the maintenance of genomic stability, and polymorphisms in the gene have been associated with both poor prognosis in osteosarcoma and susceptibility to breast cancer [ 61 , 62 , 74 , 75 ]. With deletion of the gene in mice also shown to increase cancer susceptibility, it is clear that RECQL5 is an important tumor suppressor [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%